If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+2(x+3)=5(x+2)+4
We move all terms to the left:
x+2(x+3)-(5(x+2)+4)=0
We multiply parentheses
x+2x-(5(x+2)+4)+6=0
We calculate terms in parentheses: -(5(x+2)+4), so:We add all the numbers together, and all the variables
5(x+2)+4
We multiply parentheses
5x+10+4
We add all the numbers together, and all the variables
5x+14
Back to the equation:
-(5x+14)
3x-(5x+14)+6=0
We get rid of parentheses
3x-5x-14+6=0
We add all the numbers together, and all the variables
-2x-8=0
We move all terms containing x to the left, all other terms to the right
-2x=8
x=8/-2
x=-4
| 4x+17=-4x+9 | | t=72-16 | | r+2-5=1 | | 6m+17=-m= | | 6h−2h=16 | | 21/x=14/36 | | 39=-7x-10 | | -1+14x-1+14x=180 | | 2-3x=2(1-x)-x | | 2w+2(w-50)=150 | | -6=3/2(4)+b | | 28=-4(7x-7) | | 7t+11=32 | | 21 x+4=−4 | | -9=a/3-10 | | -2(4a+4)=-8+a | | 2w+2(w+50)=150 | | 4x+100=2x+3010 | | -7=3p-7-3p | | -1(3v-8)=-28+9v | | -7y+4(y-3)=-15 | | 5x=99–6x | | 2w+50+2w=150 | | .15x=1600000 | | -2k+6(k+3)=25+3k | | (20x+3)=(9x+3) | | 35+3x=4(-x+2)-22 | | –4t−6=–3t | | -2p+5.8=6 | | -1(y+4)-3y=-16 | | y-3/5=y-5 | | 6r^2(2-3r(2-1=0 |